Telecoaching: a potential new training model for Charcot-Marie-Tooth patients: a systematic review - Leale, Ignazio; Di Stefano, Vincenzo; Costanza, Carola; Brighina, Filippo; Roccella, Michele; Palma, Antonio; Battaglia, Giuseppe (Frontiers in Neurology, 2024)
Charcot-Marie-Tooth disease (CMT) is an inherited neuropathy that affects the sensory and motor nerves. It can be considered the most common neuromuscular disease, with a prevalence of 1/2500. Considering the absence of a specific medical treatment and the benefits shown by physical activity in this population, a systematic review was completed using several search engines (Scopus, PubMed, and Web of Science) to analyze the use, effectiveness, and safety of a training program performed in telecoaching (TC). TC is a new training mode that uses mobile devices and digital technology to ensure remote access to training. Of the 382 studies identified, only 7 met the inclusion criteria. The effects of a TC training program included improvements in strength, cardiovascular ability, and functional abilities, as well as gait and fatigue. However, the quality of the studies was moderate, the size of the participants in each study was small, and the outcome measured was partial. Although many studies have identified statistically significant changes following the administration of the TC training protocol, further studies are needed, with appropriate study power, better quality, and a higher sample size.